PERBANDINGAN PEMBELAJARAN MATEMATIKA SECARA DARING DAN PEMBELAJARAN MATEMATIKA SECARA LURING TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS VII MTS GUPPI PAGAR ALAM - Arieska Efendy (Jurnal Ilmiah Mahasiswa Matematika Realistik, 2021)
Education is a form of effort that is carried out consciously and intentionally in order to change behavior and mature human beings, both individually and in groups through learning and training. The problem facing the world of education today is the weakness of the learning process. Many parties did not think that the corona virus (Covid-19) would become a pandemic that spread throughout the world, including Indonesia. The conditions faced today are indeed not easy for the world of education. The learning process is not as free as before where there is a lot of interaction between students and students, students and teachers. The purpose of this study was to determine the comparison of online mathematics learning and offline mathematics learning on the mathematics learning outcomes of seventh grade students of MTs Guppi Pagar Alam. This research is a type of quantitative approach research. This research is quantitative in nature, namely the data obtained are analyzed by statistical formulas to obtain conclusions. Based on the results of research and discussion, it can be concluded that offline mathematics learning can improve student learning outcomes for class VII MTs GUPPI Pagar Alam. This can be seen from the average value of student learning outcomes using offline learning is 70.29 while the average value of student learning outcomes without using online mathematics learning is 60.43.Keywords: Mathematics, Offline Learning, Learning Outcomes